A New Modus Operandi of Corruption: Exploring the Phenomenon of Trading in Influence - Nabila Alinka Wibowo; Zulfiani Anita (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2025)
This research discusses a new form of corruption crime in the form of influence peddling. The background of this research stems from the regulation of trading in influence in the United Nations Convention Against Corruption 2003 and the increase in the number of corruption cases. In this research, a normative type of research that is prescriptive and technical in nature is used. This research uses two approaches, namely the legislative approach and the conceptual approach. There are two issues derived from this research. How is the pattern of trading in influence characteristics? (2) How is the regulation of trading in influence in Indonesia? The results of this research on the first issue found three patterns of influence trading, namely horizontal, vertical, and vertical with intermediaries. As for the second issue, it was concluded that trading in influence is not yet regulated in Indonesian positive law, but it is regulated in the UNCAC 2003Keywords : Corruption; Criminal Offense; Trading In Influence Abstrak: Penelitian ini membahas bentuk baru kejahatan korupsi berupa perdagangan pengaruh. Latar belakang penelitian ini berasal dari regulasi perdagangan pengaruh dalam Konvensi PBB tentang Pemberantasan Korupsi 2003 dan peningkatan jumlah kasus korupsi. Dalam penelitian ini, digunakan jenis penelitian normatif yang bersifat preskriptif dan teknis. Penelitian ini menggunakan dua pendekatan, yaitu pendekatan legislatif dan pendekatan konseptual. Ada dua isu yang dihasilkan dari penelitian ini. Bagaimana pola perdagangan pengaruh? (2) Bagaimana regulasi perdagangan pengaruh di Indonesia? Hasil penelitian pada isu pertama menemukan tiga pola perdagangan pengaruh, yaitu horizontal, vertikal, dan vertikal dengan perantara. Adapun isu kedua, disimpulkan bahwa perdagangan pengaruh belum diatur dalam hukum positif Indonesia, tetapi diatur dalam UNCAC 2003.Kata Kunci: Korupsi; Tindak Pidana; Perdagangan Pengaruh